How watching sports events empowers people’s sense of wellbeing? The role of chain mediation in social interaction and emotional experience - Guo, Jiru; Yang, Hong; Zhang, Xiaoli (Frontiers in Psychology, 2024)
Background: While engaging in sports is widely recognized for enhancing well-being, limited research has examined the effects of watching sports events on individuals' subjective well-being.The mechanisms and pathways underlying this relationship remain unclear.Objectives: This study explores the correlation between watching sports events and the well-being of Chinese individuals, based on the theoretical framework of "spectator behavior → social interaction → emotional experience → happiness." The aim is to investigate the mediating effects of social interaction and emotional experience, providing insights for promoting greater participation in sports events and supporting the healthy development of the sports industry.The study involved 885 participants from five representative provinces and cities in China.Assessment tools included the Physical Activity Rating Scale, Social Interaction Questionnaire, Emotional Experience Questionnaire, and Subjective Well-Being Scale. Data were analyzed using Stata and the PROCESS plug-in of SPSS for comprehensive multivariate statistical analysis.Results: Watching sports events significantly and positively affects subjective well-being, social interaction, and emotional experience (P < 0.001). Three mediating pathways were identified: (1) watching sports events → social interaction → subjective well-being (effect size: 0.024), (2) watching sports events → emotional experience → subjective well-being (effect size: 0.011), and (3) watching sports events → social interaction → emotional experience → subjective well-being (effect size: 0.003).The direct impact of watching sports events on subjective well-being was positive.Indirect effects were facilitated by the mediating roles of social interaction and emotional experience, with the effect of social interaction being more substantial than that of emotional experience.Implications: These findings suggest that watching sports events can serve as a catalyst for enhancing well-being, primarily through fostering social connections and enriching emotional experiences. Practically, this indicates the potential value of encouraging viewership of sports events as a means of promoting community engagement and mental health, thus contributing to the holistic growth of the sports sector and public health initiatives.